Heat Transfer Performance of a Gasketed Plate Heat Exchanger Subjected to Mechanical Vibration أداء إنتقال الحرارة لمبادل حراري من النوع اللوحي مجهز بمانع تسريب يهتز إهتزازا ميکانيکيا - M. Bassiouny; A. Kabeel; A. Khalil; Y. El Samadony; A. Khaira (Journal of Engineering Research - Egypt, 2019)
Heat transfer characteristics in terms of heat transfer coefficient, overall heat transfer coefficient and heat exchangereffectiveness of a vertical counter flow Gasket plate heat exchanger (GPHE) are experimentally investigated. The testedPHE is made of stainless-steel plates with 30° chevron angle (β=30°). The surface enlargement factor, Ф for all plateswas 1.17. Six plates were installed; providing two hot channels and three cold channels in counter flow arrangement.The vibration effect on tested GPHE has been performed and compared with non-vibration model. Vibration frequencies(ω) are in the range of 13.33 to 46.67 cps and vibrational dimensionless amplitude (A/De) varied from 9.14*10-3 to52.66*10-3 at various oscillating Reynolds numbers were employed. It is found that the heat transfer performance of theGPHE is enhanced when vibration is applied. The maximum enhancement percentage of the GPHE heat transfercoefficient, overall heat transfer coefficient and effectiveness due to vibration are 43%, 31% and 18%, respectively.These maximums are occurred at oscillation Reynolds number of 211.34 and A/De = 52.66*10-3 which after theresonance condition. The GPHE performance after and before resonance condition are obtained. Finally, correlationsfor GPHE Nusselt number, when vibration is and is not applied, are obtained with an acceptable error of 3.99%.